2016
DOI: 10.1080/10495398.2016.1164179
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Putative Stem Cell Marker, Hepatocyte Nuclear Factor 4 Alpha, in Mammary Gland of Water Buffalo

Abstract: Buffaloes account for more than 56% of total milk production in India. Cyclic remodeling of mammary glands of human, mice, cow, sheep, and goat is determined by mammary stem cells. It is logical to assume that buffalo mammary gland will have mammary stem/progenitor cells. Thus far, no report exists on identification of buffalo mammary stem cells. Hepatocyte nuclear factor 4 alpha (HNF4A) is a candidate marker for hepatic progenitor cells and has recently been suggested as a marker of bovine mammary stem/progen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Water buffalos are domesticated farm animals and provide very significant portions of dairy production in several parts of Asia. There is one report in water buffalos describing identification of MaSC according to the expression of Hepatocyte Nuclear Factor 4 alpha ( HNF4α ) . HNF4α is a liver stem cell transcription factor which is highly upregulated in bovine basal label‐retaining cells and therefore suggested as a potential mammary stem cells marker .…”
Section: Characterization Of Mammary Stem Cellsmentioning
confidence: 99%
“…Water buffalos are domesticated farm animals and provide very significant portions of dairy production in several parts of Asia. There is one report in water buffalos describing identification of MaSC according to the expression of Hepatocyte Nuclear Factor 4 alpha ( HNF4α ) . HNF4α is a liver stem cell transcription factor which is highly upregulated in bovine basal label‐retaining cells and therefore suggested as a potential mammary stem cells marker .…”
Section: Characterization Of Mammary Stem Cellsmentioning
confidence: 99%
“…ALDH1 is expressed in a variety of cells, including cancer stem cells (Ginestier et al 2007). NR5A2 is a pluripotency transcription factor of adult stem cell like that of OCT4 in embryonic stem cells (Heng et al 2010), and HNF4A , FNDC3B and NOTCH1 are potential candidate markers of mammary stem/progenitor cells (Dontu et al 2004; Choudhary et al 2013, 2016; Osińska et al 2014). Fatty acid transporter genes, CD36 and FABP3 , are co-regulatory genes and have been associated with mammary cell differentiation (Spitsberg et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Others have estimated the effects of prepubertal nutrition (Daniels et al, 2009), ovariectomy (Ellis et al, 2012), or treatment with antiestrogens (Tucker et al, 2016) on populations of putative bovine MaSC via counting of LREC. Others have estimated possible populations of bovine MaSC based on counting of cells expressing HNF4A in water buffalo (Choudhary et al, 2016) or Musashi-I in mammary tissue from sheep (Colitti and Farinacci, 2009) across different stages of development. Specific to myoepithelial cells and presumptive myoepithelial progenitor cells, Ellis and colleagues (Ballagh et al, 2008;Safayi et al, 2012;Tucker et al, 2016) have shown that smooth muscle actin or common acute lymphoblastic leukemia antigen are excellent cytoplasmic markers and transformation-related protein 63 an excellent nuclear marker for basally located myoepithelial cells and their progenitors.…”
Section: Mammary Stem Cells and The Bovine Mammary Glandmentioning
confidence: 99%